Pengaruh Variasi Produk Terhadap Keputusan Pembelian pada Mixue Cabang Karawang - Priambudi; Qobus Rayhaan Al Awaludin; Abdul Yusuf (Masyarakat Ekonomi Syariah Bogor, 2024)
Mixue is a beverage outlet originating from China, founded in June 1997. Mixue began to enter Indonesian territory in 2020, Mixue outlets serve various drink menus and also ice cream. The featured menu is boba ice cream which is in demand by many people from various circles. However, there are several things that must be considered, with the emergence of several new competitors who make many product variants with varying flavors, whether this will influence the level of purchasing decisions regarding mixue. This research aims to find out whether product variations from mixue influence customers' purchasing decisions. So the mixue company can know whether it needs to increase its product variety in order to compete with its competitors.